Perceptions of the effects of clicker technology on student learning and engagement: a study of freshmen Chemistry students - Jenepher Lennox Terrion (Research in Learning Technology, 2012)
While technology – in the form of laptops and cellphones – may be the cause of much of the distraction in university and college classrooms, some, including the personal or classroom response system (PRS/CRS) or clicker, also present pedagogical opportunities to enhance student engagement. The current study explored the reactions of students to clicker implementation in a large, introductory chemistry class. During the final class of the semester, 200 students in an introductory chemistry class responded to an attitudinal and informational student survey using both Likert-type and non-Likert type questions to evaluate their perception of the implementation of the clickers and their impact on student learning and engagement. The results demonstrated that, when implemented effectively, clickers contribute to greater student engagement and, ultimately, an opportunity for professors to enact best practices in higher education pedagogy. This study points to the importance of effective pedagogy in making clickers worthwhile.